1991
DOI: 10.1128/mcb.11.1.486
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ribosomal reinitiation at upstream open reading frames in amino acid-starved cells forms the basis for GCN4 translational control.

Abstract: GCN4 encodes a transcriptional activator of amino acid-biosynthetic genes in Saccharomyces cerevisiae that is regulated at the translational level by upstream open reading frames (uORFs) in its mRNA leader. uORF4 (counting from the 5' end) is sufficient to repress GCN4 under nonstarvation conditions; uORF1 is required to overcome the inhibitory effect of uORF4 and stimulate GCN4 translation in amino acid-starved cells. Insertions of sequences with the potential to form secondary structure around uORF4 abolish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
1
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(235 citation statements)
references
References 47 publications
(72 reference statements)
11
220
1
3
Order By: Relevance
“…The presence of upstream start codons has been observed in many cellular mRNAs for transcription factor genes from yeast (GCN4), animals (jun) and plants (OPAQUE2, SN, LC, CPRF-1, MYBST1, OBF1, LIP19, MLIP15, Arabidopsis TGA1), and in some cases it has been shown that such a feature can inhibit translation of downstream coding sequences. In the case of GCN4, amino acid availability regulates GCN4 expression at the level of translational initiation (Abastado et al, 1991). Thus, the upstream ORFs (uORFs) of GCN4 constitute a translational control element that allows ribosomes to reach the start codon of the major ORF only when cells are deprived of an amino acid.…”
Section: The 5ј Leader Sequences Of the Bzip Transcriptsmentioning
confidence: 99%
“…The presence of upstream start codons has been observed in many cellular mRNAs for transcription factor genes from yeast (GCN4), animals (jun) and plants (OPAQUE2, SN, LC, CPRF-1, MYBST1, OBF1, LIP19, MLIP15, Arabidopsis TGA1), and in some cases it has been shown that such a feature can inhibit translation of downstream coding sequences. In the case of GCN4, amino acid availability regulates GCN4 expression at the level of translational initiation (Abastado et al, 1991). Thus, the upstream ORFs (uORFs) of GCN4 constitute a translational control element that allows ribosomes to reach the start codon of the major ORF only when cells are deprived of an amino acid.…”
Section: The 5ј Leader Sequences Of the Bzip Transcriptsmentioning
confidence: 99%
“…uORF stop codon and CDS initiation codon allows more time for the scanning 40S to reacquire a new eIF2⅐GTP⅐Met-tRNA i Met complex, a significant feature of the delayed translation reinitiation model that was originally identified in the yeast Saccharomyces cerevisiae for the transcriptional activator GCN4 (19,21,43) and subsequently suggested for the related mammalian ATF4 (24,33,34).…”
Section: Ribosome Reinitiation In the Isrmentioning
confidence: 99%
“…3A) (24,34). The GCN4 5Ј-leader contains four uORFs, each encoding polypeptides two to three residues in length (19,21). In the delayed translation reinitiation model, the 5Ј-proximal uORF1 in the ATF4 and GCN4 5Ј-leaders acts as a positive element that promotes downstream translation reinitiation (19,20,24).…”
Section: Delayed Translation Reinitiationmentioning
confidence: 99%
“…Of importance to this discussion of regulation of (post-) termination events are the findings that ribosomes can resume scanning after terminating translation at uORF1, and that they can subsequently acquire competence to reinitiate at downstream AUG codons (Hinnebusch, 1997). In contrast, ribosomes terminating translation at the uORF4 termination codon are released from the mRNA (Abastado et al, 1991 ;Dever et al, 1992). This key difference between the behaviour of post-termination ribosomes at uORFs 1 and 4 results from the character of the nucleotide context immediately preceding (3 nt) and following (10 nt) the respective uORF stop codons (Grant & Hinnebusch, 1994).…”
Section: Alternative Post-termination Events : Resumed Scanningmentioning
confidence: 99%